2014
DOI: 10.5539/ass.v10n7p136
|View full text |Cite
|
Sign up to set email alerts
|

Information & Communication Technology (ICT) Tools in Teaching and Learning Literature Component in Malaysian Secondary Schools

Abstract: Literature Component has been part of the English Syllabus in Malaysian secondary schools level since the year 2000. Previous researches have proven that teaching Literature component is not easy as teachers still rely heavily on the conventional methods like discussing plot, characters, theme, setting and moral values of the texts. With the advancement of Information and Communication Technology (ICT), this study is meant to explore the teachers and students' usage of ICT and their attitudes towards ICT in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 10 publications
(20 reference statements)
2
34
0
2
Order By: Relevance
“…Nowadays with the existence of ICT, students can surprisingly be creative if they are given a certain amount of time and the freedom of how they want to learn and when they want to learn as they became more motivated and responsible (Yunus, Salehi, & Chenzi, 2012;Borg & Al-Busaidi, 2012). In addition, ICT also has the capability in assisting and stimulating students to be more creative and help to develop ALL as well as improving teaching and learning quality (Yunus & Suliman, 2014). …”
Section: Developing Autonomous Language Learning Practicesmentioning
confidence: 99%
“…Nowadays with the existence of ICT, students can surprisingly be creative if they are given a certain amount of time and the freedom of how they want to learn and when they want to learn as they became more motivated and responsible (Yunus, Salehi, & Chenzi, 2012;Borg & Al-Busaidi, 2012). In addition, ICT also has the capability in assisting and stimulating students to be more creative and help to develop ALL as well as improving teaching and learning quality (Yunus & Suliman, 2014). …”
Section: Developing Autonomous Language Learning Practicesmentioning
confidence: 99%
“…Apart from that, the use of ICT integration in blended learning is a confidence boost among low proficiency students. This is also supported by Yunus and Suliman (2014) in their study that the blending of ICT in literature teaching benefits students in motivational aspects. The ability to maneuver their way using the internet to access resources related to the lesson and videos (YouTube), digital dictionaries, online games and many more shows that ICT integrated less promotes 21st century learning and students can choose the pace of the lesson in accordance to their learning ability.…”
Section: Pre Test and Post Test Findingsmentioning
confidence: 58%
“…As the use of literal meanings is common in literature, it may require special assistance from teachers to assist students' understanding. As revealed by Yunus and Suliman (2014), teachers lack ideas in making a literature lesson meaningful, and this is supported by Muthusamy et al (2017) whose study showed that most teachers claimed that teaching literature is the most difficult thing to do. On the contrary, students might face difficulties to fathom a literary text as a result of limited language mastery as affirmed by Novianti (2016) and Sunardi et al (2018), that limited language proficiency impedes students in understanding literary texts especially classical ones.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, Suliman and Yunus (2014) explain that their respondents preferred to use simpler terms in giving explanation as well as probing questions in the teaching process. Yunus and Suliman (2014) as well as Muthusamy et al (2017) come to disclose that different preferred techniques and approaches in teaching literature such as note-copying, presentation, class discussions and autonomous learning. All these studies have demonstrated that different settings may opt for different approaches in teaching literature.…”
Section: Studies On Literature Approachesmentioning
confidence: 99%
See 1 more Smart Citation